A review of the six-minute walk test: Its implication as a self-administered assessment tool - Du, HuiYun; Newton, Phillip; Salamonson, Y.; Carrieri-Kohlman, V.; Davidson, Patricia (Elsevier, 2009)
Promoting self-management and monitoring physical activity are important strategies in chronic heart disease (CHD) management. The six-minute walk test (6MWT) is a commonly used sub-maximal exercise test for measuring physical functional capacity. The aim of this paper is to review the current literature on 6MWT relating to methodological issues as well as exploring the potential of the protocol to be adopted as a self-administered exercise test. The Medline, CINAHL, Science Direct and the World Wide Web using the search engine Google, were searched for articles describing the administration, reliability and validity of the 6MWT. Findings of the integrative literature review the 6MWT is a simple, safe tool. To date, the capacity for self-administration of the 6MWT has not been investigated. Adapting the 6MWT as a patient-reported outcome measure may enhance the capacity, not only for clinicians to monitor functional status, but also promote self-management by enabling individuals to monitor changes in their functional capacity.